Cell-free synthesis of proteins with selectively 13C-labelled methyl groups from inexpensive precursors - D. Van Raad; G. Otting; G. Otting; T. Huber (Magnetic Resonance, 2023)
The novel eCell system maintains the activity of the entire repertoire of metabolic Escherichia coli enzymes in cell-free protein synthesis. We show that this can be harnessed to produce proteins with selectively 13C-labelled amino acids from inexpensive 13C-labelled precursors. The system is demonstrated with selective 13C labelling of methyl groups in the proteins ubiquitin and peptidyl-prolyl cis–trans isomerase B. Starting from 3-13C-pyruvate, 13C-HSQC cross-peaks are obtained devoid of one-bond 13C–13C scalar couplings. Starting from 2-13C-methyl-acetolactate, single methyl groups of valine and leucine are labelled. Labelling efficiencies are 70 % or higher, and the method allows us to produce perdeuterated proteins with protonated methyl groups in a residue-selective manner. The system uses the isotope-labelled precursors sparingly and is readily scalable.